2020
DOI: 10.21873/invivo.12140
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up Strategies for Primary Extremity Soft-tissue Sarcoma in Adults: A Systematic Review of the Published Literature

Abstract: Aim: Follow-up strategies for primary extremity soft-tissue sarcomas (eSTS) in adults were evaluated in a systematic review of the published literature. Material and Methods: The published literature was reviewed using PubMed. Of 136,646 studies published between 1985 and 2019, 78 original articles met the inclusion criteria. Articles were selected on the basis of the PRISMA guidelines. The selected articles were then cross-searched to identify further publications. August 1, 2019 was used as the concluding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
(215 reference statements)
0
7
1
Order By: Relevance
“…Patients with these STS subtypes are 6 times more likely to develop isolated NPM without prior evidence of or concurrent PM as compared to other subtypes of sarcomas. In comparison to a recent systematic review which suggested that leiomyosarcoma is the second most common subtype, after myxoid liposarcoma, to develop abdominal or retroperitoneal metastases, none of the 11 leiomyosarcoma patients in our cohort developed isolated or initial NPM 11 . The explanation why certain subtypes of STS have higher affinity towards NPM than other subtypes remain unclear.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Patients with these STS subtypes are 6 times more likely to develop isolated NPM without prior evidence of or concurrent PM as compared to other subtypes of sarcomas. In comparison to a recent systematic review which suggested that leiomyosarcoma is the second most common subtype, after myxoid liposarcoma, to develop abdominal or retroperitoneal metastases, none of the 11 leiomyosarcoma patients in our cohort developed isolated or initial NPM 11 . The explanation why certain subtypes of STS have higher affinity towards NPM than other subtypes remain unclear.…”
Section: Discussioncontrasting
confidence: 78%
“…All other cases of NPM occurred after or coincident with pulmonary metastatic disease. It took a median (interquartile range [IQR]) of 14 (8-28) months for NPM to occur in cases and almost half of that time for the PM to develop initially; median (IQR) of 7 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). This supports the theory that STS affinity to visceral metastases is low and the time interval until development of visceral metastases is also long.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most experts recommend regular surveillance of radiologic and laboratory workup for IMT patients who undergo resection. There are no guidelines regarding the frequency of follow-up in these rare tumors; most experience is extrapolated from the sarcoma field and many experts advise surveillance imaging every six months for the first three to five years [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tumour characteristics including location and grade have a substantial impact on the local recurrence and imply the need for follow-up imaging. 45 Routine follow-up of these patients, especially involving bone tumour, is mainly by serial radiographs. In the immediate postoperative period, the baseline radiograph is extremely important since it shows the osseous and soft tissue changes following surgery.…”
Section: Evaluation Of Suspected Tumour Recurrence Post-surgerymentioning
confidence: 99%